Análisis de los fenómenos de remoción en masa (Deslaves) en la provincia de Cotopaxi. Propuesta de soluciones - Chicaiza Chiliquinga, Segundo Ramón (2010)
The present investigation whose thematic is "ANALYSIS OF THEPHENOMENA OF mass REMOVAL (DESLAVES) IN THE COUNTY DE COTOPAXI. PROPOSAL OF SOLUTIONS" outlines, describes and proposes solutions to the problem of the interrelation between the earth movement andthe deterioration of the environmental quality in critical areas of the referredcounty. The general objective of the study was the determination of thenexuses and interrelations among the occurrence of Phenomena of MassRemoval (PMR) and the Environmental Quality in the critical areas of theCounty of Cotopaxi, among the years 1988 and 2008. Specifically, threeobjectives were reached, the identification of the occurrence of PMR in thecritical areas, the evaluation of the Environmental Quality of this areas afterthe occurrence of the phenomena and, the elaboration of the General Plan oMitigation for the county of Cotopaxi that implies the minimization of thenegative effects in the Environmental Quality, of the occurrence of FRMSeventeen critical areas belonging to the cantons Latacunga, La ManáPangua, Pujilí, Salcedo, Saquisilí and Sigchos, was identified and beingworked with a simple random sample of 399 people from a population o170716 residents. The main results obtained in the process of nonexperimental investigation were the following ones: The deterioration of theEnvironmental Quality of the critical areas, after the occurrence of the FRM, itwas evaluated, predominantly, as "very significant", being determinedconsiderable affectations in the landscape, the flora and the fauna, the civilinfrastructure, the quality of life and with less signification, the loss of humanlives. Using the distribution of Squared Ji and with a 99,5% of trust theinvestigation hypothesis was verified that outlines that "The Phenomena omass Removal affect negatively to the Environmental Quality in the critical areas of the County of Cotopaxi". Next, a General Plan of Mitigation waselaborated for the county that will imply the minimization of the negativeeffects in the Environmental Quality, of the occurrence of FRM.